Patterns of admission in forensic units during the COVID-19 pandemic: a process analysis - D’Orta, Isabella; Herrmann, François R.; Giannakopoulos, Panteleimon (Frontiers in Psychiatry, 2024)
Introduction The impact of COVID-19 pandemic on forensic service practice remains matter of debate. Increased rates of anxiety, depression, and exacerbation of psychotic symptoms were reported in the early phases of the pandemic among detained persons. However, longitudinal analyses in medium-security hospitals taking into account the whole pandemic period led to mitigated results. Methods This report examines the evolution of the type (voluntary versus involuntary) and reason of admissions, length of stay, history of outpatient care, short-term seclusion hours for aggressive behaviors, and clinical diagnoses for detainees needing acute psychiatric care during the COVID-19 pandemic in the sole secure ward located in the central prison of Geneva, Switzerland. To determine the general trend of the processes over time we applied a combination of process analysis with run chart plotting, and fractional polynomial regression. Results Run tests showed that the proportion of cases with personality disorders, substance use disorders (SUD), and previous outpatient care tended to increase during the COVID pandemic with subsequent decrease to reach the pre-COVID values. This was also the case for depressive symptoms as reason for admission. The proportion of involuntary admission showed a steady increase both during the COVID and post-COVID time periods. In contrast, short-term seclusion hours decreased during the COVID pandemic followed by a return to their pre-COVID values. Regression models revealed that the COVID pandemic was associated with a significant increase in the rates of inmates with personality disorders and SUD admitted for forensic care explaining 36 and 41% of their variance. Discussion These data support the idea that, in terms of acute care needs, the COVID-19 pandemic was associated with increased needs for acute forensic care that concerned detainees with personality disorders characterized by increased levels of impulsiveness, decreased tolerance to frustrations, loss of control, increased extraversion and frequent SUD comorbidity.